Physics ContributionsCommissioning of brachytherapy module of Oncentra MasterPlan treatment planning system - Alves de Oliveira, Carla; do Carmo Lopes, Maria; Matos, Armanda (Journal of Contemporary Brachytherapy, 2009)
Purpose: To describe the tests that have been performed in order to commission the Brachytherapy module, version 3.2, service pack 3.0, of the Oncentra MasterPlan treatment plan system (OB), from Nucletron. The results were benchmarked against those obtained with the Plato system, v 14.3.7, also from Nucletron, used in the clinical routine. Material and methods: Commissioning was performed taking Plato, v 14.3.7 as the standard TPS used in clinical practice. Commissioning tests were divided into two categories: i) simple geometric catheter configurations and ii) clinical intracavitary gynaecological and interstitial breast implants. For category i), also manual independent point dose calculations following the TG-43 dosimetry protocol were included in the comparisons. For category ii), the treatment plan comparisons were based on the calculated dose distributions in CT axial plans and on the dose-volume quality indexes following the local clinical acceptance criteria. Similar optimization tools were used in both systems. IPSA in OB was tested for planning interstitial breast implants and compared with the optimization process used with Plato in the clinical routine. Results and Conclusions: Regarding the point dose calculations, the agreement was better than 1%. For the clinical compared cases and using the same optimization tools all plans ended in similar dose distributions and very close quality indexes. Nevertheless, for endovaginal treatment plans, a slightly different value for the DTGR parameter had to be used (0.452, instead of 0.5 used as default in PLATO) in order to achieve the same dwell time for each activated source dwell position. Concerning interstitial breast implants, the IPSA algorithm constitutes a fast tool to reach a close clinical acceptable solution but Graphical Optimization is still needed. Considering these results the OB module was accepted for clinical use despite some persisting limitations, such as no consideration of heterogeneities or options for applicator shielding.